The utility of a novel colonoscope with retroflexion for colorectal endoscopic submucosal dissection - Tanaka, Hidenori; Oka, Shiro; Tanaka, Shinji; Inagaki, Katsuaki; Okamoto, Yuki; Matsumoto, Kenta; Boda, Kazuki; Yamashita, Ken; Sumimoto, Kyoku; Ninomiya, Yuki; Hayashi, Nana; Chayama, Kazuaki (Endoscopy International Open, 2019)
Background and study aims The PCF-H290TI/L produced by Olympus is a novel colonoscope equipped with some advantageous features for endoscopic treatment. It is expected to improve the potential for retroflexion and overall endoscope operability, which can reduce the difficulty of performing colorectal ESD. The aim of this study was to evaluate the utility of the novel colonoscope in colorectal ESD.Methods Three hundred and forty-eight consecutive colorectal lesions resected via ESD between June 2014 and January 2017 at Hiroshima University Hospital were included in the retroflexion ability analysis. We compared the retroflexion potential of PCF-H290TI to that of a conventional endoscope. Two hundred and twenty-seven colorectal lesions located in the left-sided colon and resected with ESD between April 2009 and February 2018 were enrolled in the treatment outcome analysis. Treatment outcomes using PCF-H290TI compared to those of the conventional colonoscope, and outcomes of the PCF-H290TI with retroflexion compared to those of the conventional colonoscope without retroflexion were evaluated by propensity score matching.Results The retroflexion rate with the PCF-H290TI was 76 %, which was significantly higher than the 44 % rate with the conventional scope. Endoscope operability was better and dissection speed was faster when using the PCF-H290TI with retroflexion compared to the conventional colonoscope without retroflexion. There were no significant differences between the groups in en bloc resection rate and adverse events.Conclusion Compared to the conventional colonoscope, the PCF-H290TI/L made it easier to perform ESD via a retrograde approach regardless of tumor location, and thus may be useful for performing colorectal ESD.